Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 1. Beitrag. Bericht über den Verlauf der Reise. - Friese, Gerrit; Königsmann, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1962)
The authors present a general report on their entomological expedition to Albania (9.5.-16.8. 1961). There are given in a general part details on history, population, geography, geology, climatology, vegetation and fauna (exclusive insects) of the country. The history of the entomological investigation of Albania is discussed. Further chapters deal with the equipment, the collecting methods, preparation, conservation and carriage of the material. The course of the expedition and the collecting places are described as to their geography, geology, climate, vegetation, and fauna. A total of more than 41.000 specimens of insects were collected. A detailed scientific investigation of this material by specialists is to be published at times in this periodical.